The Pengaruh Sistem Informasi Akuntansi dan Motivasi Kerja Terhadap Kinerja Pegawai di Badan Pengelolaan Keuangan dan Pendapatan Daerah (BPKPD) Provinsi Jambi - Nuraimah Nuraimah; Eri Bestary Al Haitamy; Ferdyan Wana Saputra (Journal of Applied Accounting And Business, 2025)
This study aims to provide the impact of accounting information systems and work motivation on employee performance at the Regional Revenue and Financial Management Agency (BPKPD) of Jambi Province. This study is expected to provide clear insight into the importance of accounting information systems and work motivation in improving employee performance and providing suggestions for BPKPD human resources. This study uses a quantitative method with a descriptive approach, where data collection is carried out through surveys and questionnaires. Data collection was carried out using the Random Sampling method. The number of samples used was 35 people consisting of employees who work in the human resources department. Data collection took place through the distribution of several questionnaires. The measuring instrument used in this analysis was the SPSS version 30.0 program. The results of the analysis of this study indicate that the accounting information system variable partially does not have a significant effect on employee performance, while the work motivation variable partially has a significant effect on employee performance. Meanwhile, the accounting information system variable and work motivation simultaneously have a significant effect on employee performance.